2012
DOI: 10.1111/epp.2556
|View full text |Cite
|
Sign up to set email alerts
|

Tuta absoluta, a South American pest of tomato now in the EPPO region: biology, distribution and damage

Abstract: Tuta absoluta (Meyrick) is an invasive pest of tomato native to South America, where it is responsible for extensive damage. It rapidly spread into several European countries, becoming a key pest. Knowledge of its main biological traits can be used to develop effective plant protection management strategies. It is a multivoltine species with a homodynamous behaviour, and the length of its life cycle depends on environmental conditions, particularly temperature. The larvae feed and develop inside tomato leaves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 22 publications
3
79
0
2
Order By: Relevance
“…Since the time of its initial detection, it has caused serious damage to tomato crops in invaded areas and it is currently considered a major agricultural threat to European and North African tomato production (Abd El-Ghany et al 2016). Although its main host is tomato, it also affects other Solanaceae, whether cultivated or not (Tropea Garzia et al 2012). The control of T. absoluta is difficult due to its miner habit, short life cycle, and high reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the time of its initial detection, it has caused serious damage to tomato crops in invaded areas and it is currently considered a major agricultural threat to European and North African tomato production (Abd El-Ghany et al 2016). Although its main host is tomato, it also affects other Solanaceae, whether cultivated or not (Tropea Garzia et al 2012). The control of T. absoluta is difficult due to its miner habit, short life cycle, and high reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae feed on the mesophyll of all aerial parts of the plants, as well as on the fruits, resulting in significant yield losses, cosmetic damages, and rot diseases to fresh market tomatoes. During the last decade, the pest has spread worldwide and is now a serious threat to commercial tomato production in South and Central America as well as in Europe (Desneux et al 2010(Desneux et al , 2011Tropea Garzia et al 2012). Since its introduction in Europe in 2006, the moth is reported on the EPPO A2 list of species recommended for regulation as quarantine pests (EPPO/OEPP 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although causing large injuries on tomatoes, T. absoluta is considered as a polyphagous leafminer that can also develop on alternative hosts such as cultivated Solanaceae including eggplant (Solanum melongena L.), sweet pepino (Solanum muricatum L.), potato (Solanum tuberosum L.), and tobacco (Nicotiana tabacum L.) (Desneux et al 2010(Desneux et al , 2011. Wild plant species have also been cited to be potential hosts for the development of the pest, such as deadly nightshade (Atropa belladonna L.), Jimson weed (Datura stramonium L.), and black nightshade (Solanum nigrum L.) (Desneux et al 2010(Desneux et al , 2011Tropea Garzia et al 2012), that can be found indifferently in croplands, wastelands, logging, and urban areas (Lambinon et al 2004). In this context, host plant species in the wild could provide reservoirs or refuges for T. absoluta.…”
Section: Introductionmentioning
confidence: 99%
“…T. absoluta shows preference for new buds, flowers and new fruits thereby making it easy to detect on affected plants. The characteristic mines on plant leaves are also an indicator of attack in addition to appearance of black frass on fruits where infestation is severe (Tropea et al, 2012).…”
Section: Host Range Of T Absolutamentioning
confidence: 99%